2016
DOI: 10.1016/j.jad.2015.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of physical health and bipolar symptoms: The intersection of mental and physical health

Abstract: Background Affective symptoms and medical comorbidities have a negative impact on the course of bipolar disorder. The aim of this analysis was to examine how the perceptions of physical health and functioning in individuals with bipolar disorder relate to their mood symptoms. Methods We analyzed longitudinal data from the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) on the physical subscales of the Short Form Health Survey (SF-36) (physical functioning, role limitations due to phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…Contrary to what could have been expected (Bernstein et al, 2016), no association between depression symptomatology and self-reported pain has been found in the present study.…”
contrasting
confidence: 99%
“…Contrary to what could have been expected (Bernstein et al, 2016), no association between depression symptomatology and self-reported pain has been found in the present study.…”
contrasting
confidence: 99%
“…Therefore, one assumes that BD, by inflicting intense psychic suffering, may cause unfavorable self-analysis in these subjects, regardless of the presence of mood symptoms, resulting in the low scores found in this work. On the other hand, our results confirm the idea that bipolar patients, even when they achieve full clinical remission, show difficulties in returning to their previous level of functioning [8][9][10] . These findings point to the need of greater care to these individuals, even when euthymic, since unfavorable self-analysis can contribute to more social isolation behaviors, more hopelessness and greater chances of new episodes of the disease.…”
Section: Dear Editorsupporting
confidence: 86%
“…Specifically, approximately 65% of depressed patients and 29% of bipolar patients report experiencing pain (e.g., migraine, chronic pain) [74, 75]. In bipolar disorder, perceptions of physical health, including bodily pain, physical functioning, and general health, are associated with worse course of illness [76]. This finding highlights that pain is considered a primary and important component of one’s physical health in mood disorders and demonstrates the importance of a treatment that targets mental and physical health outcomes in this clinical population.…”
Section: Exercise and Comorbid Conditions With Mood Disordersmentioning
confidence: 99%